HYBRID-EDFA / RFA (GABUNGAN PENGUAT OPTIK PADA TRANSMISI SERAT OPTIK) - Yuniarti, Harumi; Su’udi, Bambang Cholis (Jurnal Teknik Elektro, 2008)
The increasing demand for telecommunication services nowadays, particularly in optical fiber transmission, has necessitated the optimization of optical amplifying device, such as Erbium Doped Fiber Amplifier (EDFA). The latest development of technology has enabled the implementation of Raman Amplifier in the long haul system (300-800 km) and ultra long haul system (>900 km). The Raman Fiber Amplifier (RFA) is recommended for several advantages, such as flat gain for all wavelengths, low noise figure, and applicable to any kind of optical fibers. It is quite possible that by using C + L Band approach, much higher raise in the band Hybrid EDFA/RFAâs amplification factor can be achieved. Keywords : Optical Amplifier, EDFA, Raman Fiber Amplifier (RFA), Hybrid amplifier, Noise Figure, Gain, Optical Communication.